Vida Saludable: Etiquetas de Suplementos Dietéticos Búsqueda por Palabras: FCS8854span/FY1039, 6/2006 - Shelnutt, Karla P. (EDIS, 2008)
FCS8854-Span, a 1-page handout by Karla P. Shelnutt, is the Spanish-language version of FCS-8854, Healthy Living: Dietary Supplement Labels Word Search. It includes words that may be found on dietary supplements labels in a word search format. Published by the UF Department of Family Youth and Community Sciences, June 2008.